1994
DOI: 10.1193/1.1585773
|View full text |Cite
|
Sign up to set email alerts
|

A Basis for Evaluation of Seismic Hazard and Design Criteria for Saudi Arabia

Abstract: This paper presents the fundamental issues and policy decisions that formed the basis of the hazard and design aspects of a comprehensive research project conducted for development of the preliminary seismic design criteria for the Kingdom of Saudi Arabia. The study represents the first regionally consistent and systematic collection and critical treatment of the limited historical and instrumental data on earthquakes and seismotectonics of the region, and development of seismic design criteria. The developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 0 publications
4
27
0
Order By: Relevance
“…Depending on the nature and depth of local soil deposits, the intensity of the seismic ground motions may be amplified and the frequency characteristics of the motions significantly (Thenhaus et al 1986;Al-Haddad et al 1994) indicated that the average value of PGA is about 100 cm/s 2 through area of study, but this value did not take the local site amplification factor into account. Recently and through the first microzoning study of the Yanbu metropolitan area Alyousef et al 2014), it is illustrated that the presence of very soft to soft sediments may amplify the ground motion more than six times that of bedrocks.…”
Section: Frequency-magnitude Relationshipmentioning
confidence: 95%
“…Depending on the nature and depth of local soil deposits, the intensity of the seismic ground motions may be amplified and the frequency characteristics of the motions significantly (Thenhaus et al 1986;Al-Haddad et al 1994) indicated that the average value of PGA is about 100 cm/s 2 through area of study, but this value did not take the local site amplification factor into account. Recently and through the first microzoning study of the Yanbu metropolitan area Alyousef et al 2014), it is illustrated that the presence of very soft to soft sediments may amplify the ground motion more than six times that of bedrocks.…”
Section: Frequency-magnitude Relationshipmentioning
confidence: 95%
“…According to seismic maps, most of the Kingdom regions are no-and low-risk levels. Areas along the western coast, especially in the northwest and southwest are considered to be of moderate risk level [13].…”
Section: Typical Building Structuresmentioning
confidence: 99%
“…The earliest study for the Kingdom of Saudi Arabia (KSA) was performed by Thenhaus et al [80], in which peak ground acceleration (PGA) and velocity (PGV) were estimated for stiff soil and for 10% probability of being exceeded in 100 years using several ground motion prediction equations (GMPE). Al Haddad et al [8,9] used these ground-motion models to estimate PGA for 10% of being exceeded in 50 years and suggested seismic zonation map for KSA to be used as a basis for seismic design. Seismic hazard for particular areas in KSA and the neighboring countries was analyzed by Deif et al [36] (Sinai Peninsula and Gulf of Aqaba area, PGA and spectral acceleration for rock sites, single GMPE); Deif et al [37] (area of construction of Makkah-Madinah high-speed rail, PGA and spectral acceleration for rock sites, consideration of several GMPEs in logic tree scheme); Osman [56] GMPE); Al-Malki and Al-Amri [11] (southwestern part of KSA, PGA and spectral acceleration were estimated for bedrock and sedimentary rock sites on the basis of semi-theoretical ground-motion models obtained by stochastic simulation); Al-Arifi et al [7] (northwestern part of KSA, PGA and spectral acceleration for rock sites, single GMPE).…”
Section: Introductionmentioning
confidence: 99%
“…However the number of documented large earthquakes in the Arabian Peninsula is low due to sparsity of population. The seismotectonic setting around Saudi Arabia suggests that large earthquakes can occur along the Red Sea rift zones, Arabian Gulf and Zagros belt [4,6,8,39,40,45,60,64,66,78,79,82]. Design of buildings and structures in earthquake prone regions, seismic risk estimation and management, and insurance business require information related to expected seismic effect; the expected effect should be expressed in terms of earthquake ground-motion parameters, such as seismic intensity, peak amplitudes of ground motion, pseudo-spectral acceleration (PSA) and ground-motion time histories.…”
Section: Introductionmentioning
confidence: 99%